Analisis Strategi Pemasaran Bunga Potong Di Ilomata Florist Kelurahan Kakaskasen II Kecamatan Tomohon Utara Kota Tomohon - Pabiaran, Melsi Syandika; Kaunang, Rine; Benu, Noortje Marsellanie (Sam Ratulangi University, 2023)
This study aims to analyze the marketing strategy of cut flowers at Ilomata Florist, Kakaskasen II Village. This research was conducted from April to June 2023. The data used in this research are primary data and secondary data. The sampling technique in this study was using purposive sampling technique. The number of respondents in this research was 10 respondents. This study uses questionnaires and interviews to determine variable indicators on internal factors and external factors then determines weights and ratings using questionnaires and then determines the marketing strategy at Ilomata Florist. Data analysis method used is SWOT analysis. The results of the study showed that Ilomata Florist has a SO strategy, namely Ilomata Florist utilizes the Tomohon area as a city with the title of flower city which can easily reach consumers. Good product quality is also always maintained by Ilomata florists in an effort to retain old customers at reasonable prices. Ilomata Florist is also in quadrant I, namely being able to take advantage of strengths and opportunities as well as minimize weaknesses and prevent threats.